On the properties of null subjects in Sign Languages: the case of French Sign Language (LSF) - Jaber, A.; Carlo Geraci; Donati; C. (The linguistic review, 2022)
The typology of subject omission in simple declarative sentences ranges from languages that simply do not allow it like English and French to languages that allow it as long as it a minimum degree of topicality is guaranteed like Chinese and Japanese. In between there are various languages in which subject omission is licensed, for example by rich agreement like in Italian and Spanish, or by a particular set of grammatical features like first and second person in Finnish, or tense like in Hebrew. In other languages subject omission is only limited to expletive sentences like in German. This rich typology observed in spoken languages is also attested across sign languages, with one important exception: there is no known sign language disallowing subject omission categorically. The goals of this paper are twofold: first, we apply syntactic and semantic tests to assess the boundaries of subject omission in French Sign Language and characterize it within the typology; second, we discuss in light of some particular aspects of grammars in the visual modality this apparent anomaly of sign languages.